2022
DOI: 10.1021/acscatal.2c04207
|View full text |Cite
|
Sign up to set email alerts
|

Gold–Rhodium Nanoflowers for the Plasmon-Enhanced CO2 Electroreduction Reaction upon Visible Light

Abstract: Bimetallic nanostructures combining catalytic and plasmonic properties are a class of materials that might possess improved efficiency and/or selectivity in electrocatalytic reactions. In this paper, we described the application of gold−rhodium core− shell nanoflowers (Au@Rh NFs) as a model system for the electrochemical CO 2 reduction reaction. The nanoparticles consist of a gold nucleus surrounded by rhodium branches, combining Au localized surface plasmon resonance (LSPR) in the visible range of the spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Notably, the optimized Ni 3 S 2 @CuAg-10 exhibited remarkable catalytic activity, reaching a current density of 340.5 mA cm −2 and demonstrating outstanding stability, with a current density retention of 93% after 2 h. The enhanced catalytic activity and great stability can be attributed to the abundant catalytic activity sites resulting from the optimized configuration of the nanoflower structure. 30,31 The successful improvement in both catalytic activity and great stability in this study suggests the potential application of this strategy for the synthesis of similar catalysts. This approach provides a promising platform for the development of cost-effective catalysts with superior electrocatalytic performance.…”
Section: T H Imentioning
confidence: 66%
“…Notably, the optimized Ni 3 S 2 @CuAg-10 exhibited remarkable catalytic activity, reaching a current density of 340.5 mA cm −2 and demonstrating outstanding stability, with a current density retention of 93% after 2 h. The enhanced catalytic activity and great stability can be attributed to the abundant catalytic activity sites resulting from the optimized configuration of the nanoflower structure. 30,31 The successful improvement in both catalytic activity and great stability in this study suggests the potential application of this strategy for the synthesis of similar catalysts. This approach provides a promising platform for the development of cost-effective catalysts with superior electrocatalytic performance.…”
Section: T H Imentioning
confidence: 66%
“…Their work demonstrated that Au NR showed enhanced CO 2 RR, whereas the Pt/Au NR promoted HER upon LSPR excitation. Rodrigues et al [72] also observed that the most significant activity for CO production in Au 82 Rh 18 was achieved under 420 nm LED incidence. This wavelength aligns with the Rh LSPR excitation and Au interband transition.…”
Section: Advances In Plasmonic-assisted Electrocatalysis For Co 2 Rrmentioning
confidence: 90%
“…45,46 It is reported that the effective capacitance (C eff ) value is related to ''surface cleanliness'', in other words, an increase in the number of adsorbed species on the surface will lead to a decrease in the C eff value. 26 Due to the larger aspect ratio of Cu NAs, the electrochemical active surface area is significantly enlarged, resulting in a higher C eff (on the order of mF) compared to spherical nanomaterials reported in the literature (on the order of mF). 47 The C eff values increased significantly with the increase of potentials after À0.65 V RHE under both dark and light conditions, as depicted in Fig.…”
Section: Pec Tests For Quantitative Analysis Of Plasmonic Effectsmentioning
confidence: 99%
“…22,23 The plasmonassisted CO 2 reduction reaction (CO 2 RR) provide a sustainable and environmentally friendly approach by harnessing solar energy. 24,25 Plasmon-assisted CO 2 RR systems, such as Au@Ru core-shell nanoflowers and Ag nanopyramids, [26][27][28] have shown great potential not only in improving the activity but also in enhancing the selectivity, as described in several reports. The increase in activity (including current density and product yield) is commonly attributed to the presence of hot carriers or photothermal effects.…”
Section: Introductionmentioning
confidence: 98%